The illustrated guide to the mass communication research project - Swann, Patricia 1960- (Routledge, 2023)
"This book makes mass communication research projects more accessible to the new student researcher through a balance between an academically rigorous guide and an informal and humorous student-centered approach. The Illustrated Guide to the Mass Communication Research Project's unique, visual approach brings to life concepts and tactics under discussion through vivid illustrations. The book follows the universal format of the academic research paper: abstract, introduction, literature review, methodology, hypotheses/research questions, quantitative and qualitative analysis/findings, discussion and conclusion. It guides the reader through using key methods central to much of mass communication research: observation, interviews, focus groups, case studies, content analysis, surveys, experiments, and sampling. Each chapter contains examples of the segment under discussion, using excerpted research studies that provide writing models for the student's own research report. Ideal for students in research-centered courses in mass media, communication studies, marketing, and public relations, whether at the undergraduate or graduate level, this text will continue to serve as a valuable resource into a future communications and marketing career. Online resources are provided to support the book: examples of an in-depth interview guide, a focus group moderator guide, a content analysis coding form, observation field notes and an experiment cover story; templates for a personal SWOT analysis and an informed consent form; a research topic worksheet; a literature review matrix; and coding exercises. Please visit www.routledge.com/9781032080758"--